Chlamydia trachomatis antimicrobial susceptibility in colorectal and endocervical cells. (25th October 2017) - Foschi, Claudio; Salvo, Melissa; Cevenini, Roberto; Marangoni, Antonella
Abstract: Background: Rectal Chlamydia trachomatis infections represent one of the most common sexually transmitted infections in the MSM population. Although current treatment guidelines suggest the use of either azithromycin or doxycycline, several clinical studies reported on azithromycin treatment failures in the case of rectal C. trachomatis localizations. In this context, the biological reasons behind the lack of azithromycin efficacy for C. trachomatis infections at the rectal level are still poorly understood. Objectives: To evaluate the in vitro antimicrobial susceptibility of several C. trachomatis strains in two different cell lines, mimicking the urogenital localization and the rectal site of infection. Methods: The susceptibility to macrolides (i.e. azithromycin and erythromycin), doxycycline and levofloxacin was assessed for 20 C. trachomatis strains, belonging to the most frequently reported genovars (D, E, F and G), both in human endocervical cells (HeLa cells) and in colorectal cells (Caco-2 cells). Moreover, a correlation between MIC values and C. trachomatis bacterial load was investigated in both cell lines. Results: For all the C. trachomatis strains, regardless of the genovar, macrolides showed higher MIC and MBC values (2-fold dilutions) in Caco-2 cells compared with HeLa cells, whereas for doxycycline and levofloxacin, no significant differences were found between the two cell lines. Moreover, azithromycin MICs were significantly higher with increasing levels of C. trachomatis elementary bodies on Caco-2 cells. Conclusions: The higher azithromycin MICs observed in colorectal cells, together with the positive correlation between MICs and C. trachomatis loads found, could explain azithromycin treatment failure for C. trachomatis infections at the rectal site.